The deep blue sea : a book of colors - Wood, Audrey; Wood, Bruce Robert (New York : Blue Sky Press, 2005)
Introduces the colors of the rainbow--and more--through simple verse and vibrant illustrations of a tropical island in the middle of the sea.
3.4
K-3
Keywords: Color -- Juvenile fiction; Color -- Fiction; Color -- Fiction